Triptolide Inhibits Osteoclast Differentiation and Bone Resorption In Vitro via Enhancing the Production of IL-10 and TGF-β1 by Regulatory T Cells - Huihui Xu; Hongyan Zhao; Cheng Lu; Qi Qiu; Gui Wang; Jing Huang; Minghui Guo; Baosheng Guo; Yong Tan; Cheng Xiao (Mediators of Inflammation)
Triptolide, a purified component of Tripterygiumwilfordii Hook F, has been shown to have immunosuppressive and anti-inflammatory properties in rheumatoid arthritis (RA). Although triptolide has demonstrated that it could suppress bone destruction in collagen-induced mice, its therapeutic mechanism remains unclear. Many studies have investigated the effect of triptolide on Tregs and Tregs-related cytokine involved in RA. Additionally, previous studies have implied that Tregs inhibit osteoclast differentiation and bone resorption. Thus, in this study we aimed to explore the regulatory mechanism by which triptolide influences the Treg-mediated production of IL-10 and TGF-β1 to affect osteoclast differentiation and bone resorption. In cocultures system of Tregs and mouse bone marrow macrophages (BMMs), Tregs inhibited the differentiation of osteoclasts and reduced the resorbed areas significantly and the production of both IL-10 and TGF-β1 was upregulated. When the coculture systems were pretreated with triptolide, they produced higher levels of IL-10 and TGF-β1. Our data indicate that triptolide enhances the suppressive effects of Tregs on osteoclast differentiation and bone resorption by enhancing the secretion of IL-10 and TGF-β1. Tregs are most likely involved in the triptolide-mediated regulation of bone metabolism and may provide a potential therapeutic target for the treatment of inflammatory bone destruction.